A novel one-step biotransformation of cortexolone-21-acetate to hydrocortisone acetate using Cunninghamella blakesleeana ATCC 8688a - Jiradej Manosroi (2018)
A novel one-step biotransformation of cortexolone-21-acetate to hydrocortisone acetate by nine microorganisms in various culturing conditions including the inoculum density, pH of the medium, amounts of the precursor and surfactant or oil containing medium was presented. The microorganisms used were Cunninghamella blakesleeana ATCC 8688a, C. blakesleeana ATCC 8688b, Curvularia lunata ATCC 12017, Aspergillus niger TISTR 3245, Curvularia sp. TISTR 3289, Curvularia sp. TISTR 3291, Cunninghamella echinulata F 1307943, C. lunata F 14894 and Penicillium sp. F 879414. C. blakesleeana ATCC 8688a gave the highest yield of 85.6 ± 6.2% at the initial cell number of 1 × 103CFU, pH 6.5 and incubated for 24 h. The result from this study can not only be applied for the chemical synthesis processes which involve the hydroxylation reaction, but also an attractive approach for industrial production because of lower cost, less time consuming and more environmental friendly. © 2007 Elsevier Inc. All rights reserved.